Vocabulary in Textbooks: Issues of Selection and Instruction - Poudel , T. N.; Kattel, Achut Raj (Medha: A Multidisciplinary Journal, 2023)
Actually, this study initiated with one of the research questions: what criteria or bases there are to be applied for selecting vocabulary to mention in textbooks for instruction. And very interestingly, if not surprisingly, the study reached the conclusion that textbooks in themselves are one of the criteria for vocabulary selection. Rather than reviewing vocabulary instruction methodology, a comprehensive approach to factors aligned to vocabulary instruction is another major concern of the study. And it is found that the conventional understanding of vocabulary instruction as instruction merely on semanticity alone is partial. The role of mental lexicon, metrical stress, spaced frequency and many such subtle issues over vocabulary instruction are crucial. The terminologies ’The world of a word’ and ’The word of the world’, as well as the concept under ’Framework for word understanding’ deserve nobility. Though it was not possible to cover all that in this study, yet, it gives way to develop memory architecture for vocabulary study as a branching issue for another study.